Penerapan Model Arima Untuk Peramalan Jumlah Orang yang Melakukan Pembayaran Pajak Reklame Dispenda - Rima Aprilia; Aulia Rahman Siregar; Nurmala Sari Siregar; Irfan Suhendra; Fariz Hakim Fernanda (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The forecasting of advertisement tax payments at the Medan City Revenue Agency aims to support planning and decision-making regarding advertisement tax revenue from 2021 to 2023, covering the period from January to December. In this process, historical data on advertisement tax payments is analyzed to determine the most suitable ARIMA model by considering the Autoregressive (AR), Differencing (I), and Moving Average (MA) parameters. The research indicates that the ARIMA model can provide accurate predictions of advertisement tax payment trends, thereby serving as a tool to enhance the effectiveness of local tax management. For the period from January to October 2024, it is estimated that 1,141 individuals will make advertisement tax payments, with the lowest forecasted number occurring in January 2024 at 1,128 individuals.